Investigation of Particulate Matter (PM10) Pollution in Ipoh City, Malaysia - Ibrahim, Mohd Hairy; Mohd Isa, Nor Kalsum; Hashim, Mohd Hashiq; Ismail, Kamarul; Ariffin, Khairi; Shafii, Haryati; Muhamad Ismail, Mohd Ihsan; Sharif Ali, Sharif Shofirun; Saputra, Aditya; Che Omar, Mohd Hishamudin (International Journal of Integrated Engineering, 2021)
Air pollution is one of the phenomena that adversely affect the environment and negatively impact human health. Air pollution occurs when there are excessive air pollutants in the atmosphere. This study aims to identify and discuss the sources of PM10 emissions according to land use around Ipoh using descriptive and boxplot analysis. There are five areas selected as a sampling location for this study: Ipoh, Lahat, Chemor, Tanjung Rambutan, and Simpang Pulai that located in Hulu Kinta and Sungai Raya district. This sampling location’s primary focus is located around Ipoh city, concentrated in the industrial area. Ten land use-based sampling stations are selected to measure. PM10 data were recorded for one week during working and non-working days in July 2020 on 10 sampling stations around Ipoh. The result shows PM10 concentrations consist of industrial, infrastructure and utility, commercial, residential, and recreational areas, as shown PM10 values â€‹â€‹were recorded for one week during working days and non-working days on 10 observation stations using Portable Laser Aerosol Spectrometer and Dust Monitor Model 1.108. Based on the observations, two stations show the daily average mean of PM10 exceeding 100 Î¼g/m3 outlined in the Malaysian Ambient Air Quality Standard (MAAQS) at S6 (175.78 Î¼g/m3) and S10 (103.79 Î¼g/m3). This situation is driven by the presence of limestone-based industrial areas as well as quarrying activities. The findings also show that PM10 concentration is higher during working days rather than non-working days. Overall, PM10 concentrations that exceed the limit will have a detrimental effect on the environment and human health.